Kartu Gambar Dan Video: Inovasi Media Pembelajaran Pendidikan Agama Islam Dalam Meningkatkan Keterampilan Sosial Siswa - Mahendra, Arivan (Lembaga Peneltian Universitas Islam Internasional Darullughah Wadda'wah, 2025)
This article aims to analyze the importance of learning media innovation and the challenges faced by teachers and students in utilizing Islamic Education learning media at SD Negeri 8 Tanjung Lago. This research uses a qualitative approach, which aims to provide an in-depth description of the innovation of Islamic Religious Education (PAI) learning media at SD Negeri 8 Tanjung Lago. The data collection techniques used include interviews, observation and documentation. The data collected was then analyzed using content analysis techniques. Learning media innovation in Islamic Religious Education (PAI) has an important role in improving the quality of learning and students' understanding of the material. The use of varied media in SD Negeri 8 Tanjung Lago such as pictures, cards, videos, and other props helps visualize abstract concepts in religious teachings, making it easier for students to understand. The positive impact of implementing learning media innovations is seen in various aspects, including improved student understanding, motivation and learning outcomes. With richer learning experiences, students not only understand religious teachings more deeply, but also develop social and interpersonal skills through collaborative activities. In addition, media innovation also spurs teachers' creativity in designing more interesting and relevant learning activities.